Activation of the alternative complement pathway with rabbit erythrocytes by circumvention of the regulatory action of endogenous control proteins - Fearon, DT (The Rockefeller University Press, 1977)
Cleavage of C3 by the alternative complement pathway occurs in at least two distinct phases: continuous low grade generation of C3b by the interaction of native C3, B, D, and P, and subsequent amplified cleavage of C3 by the interaction of C3b, B, D, and P which forms the amplification convertase, P,C3b,Bb. Transition to C3b-dependent amplification is necessary to achieve substantial C3 cleavage and is normally limited by the combined action of C3b inactivator (C3bINA) and βlH. An activator of the alternative pathway, such as rabbit erythrocytes (E(r)), provides sites that protect bound C3b and P,C3b,Bb from the action of these regulatory proteins and permits C3b deposited by the low grade fluid phase reaction to assemble a membrane-associated amplification convertase which can deposit additional protected C3b. Under conditions in which the control proteins, C3bINA and β1H, almost completely inactivated C3b bound to sheep erythrocytes (E(s)), which does not activate the alternative pathway, the function of C3b bound to E(r) was diminished by less than one-fifth. Further, the P- stabilized amplification convertase on E(r) was 10-fold less sensitive to β1H-mediated decay-dissociation than the convertase on E(s). The addition of E(r) to a regulated mixture of purified C3, B, D, P, C3bINA, and β1H resulted in amplified inactivation of C3 and B by formation of the amplification convertase on E(r) as indicated by its lysis with subsequent exposure to C3-C9. In contrast, E(s) did not advance the low grade fluid phase inactivation of C3 and B to amplified inactivation and the cell was not converted to an intermediate susceptible to lysis by C3- C9. Since E(r) and E(s) did not differ in their inefficient fixation of C3b generated during an unregulated fluid phase reaction, the activating capacity of E(r) must reside in its protection of bound C3b and P, C3b,Bb from the regulatory proteins rather than in enhanced capacity to bind C3b from the fluid phase. When the reaction is limited to low grade fluid phase turnover, introduction of E(r) but not E(s) results in a 100-fold increase in the deposition of C3b, indicating that surface-dependent activation of the alternative pathway is characterized by efficient deposition of C3b on the initiating surface. Thus, the activating surfaces advance the interaction of the alternative pathway proteins to the amplification phase because of the selective inability of the regulatory proteins to deal with their substrates when deposited on these surfaces and results in a specificity that is not necessarily dependent on adaptive immunity.